THE EFFECT OF ACTIVITY-BASED PROBLEM SOLVING LEARNING ON PROBLEM SOLVING ABILITY OF TENTH GRADE STUDENTS AT SMA NEGERI 2 PALEMBANG - Rahma Amsar Napenty; Cecil Hiltrimartin (Lentera Sriwijaya : Jurnal Ilmiah Pendidikan Matematika, 2023)
The low ability of problem solving is caused by students who are not actively involved in the learning process. Student activity is needed to develop ideas and knowledge in solving mathematical problems. This study aims to see the effect of student activity-based problem solving learning on the problem solving abilities of class X students of SMA Negeri 2 Palembang. This research is a quantitative study with a one group pretest-posttest design with a sample of 35 students who were selected using a cluster sampling technique. After the Pretest and Posttest were carried out, the researcher conducted a normality test with the help of the SPSS application using the Kolmogorov Smirnov Test. Test the hypothesis using the t test for the dependent sample. Based on the test results, it was found that the significance value was 0.000 and <0.05, which meant that there was a significant influence between students' problem solving abilities before and after learning student activity-based problem solving.